Cezanne (OTUD7B) regulates HIF-1α homeostasis in a proteasome-independent manner - Bremm, Anja; Moniz, Sonia; Mader, Julia; Rocha, Sonia; Komander, David (EMBO reports, 2014)
The transcription factor HIF‐1α is essential for cells to rapidly adapt to low oxygen levels (hypoxia). HIF‐1α is frequently deregulated in cancer and correlates with poor patient prognosis. Here, we demonstrate that the deubiquitinase Cezanne regulates HIF‐1α homeostasis. Loss of Cezanne decreases HIF‐1α target gene expression due to a reduction in HIF‐1α protein levels. Surprisingly, although the Cezanne‐regulated degradation of HIF‐1α depends on the tumour suppressor pVHL, hydroxylase and proteasome activity are dispensable. Our data suggest that Cezanne is essential for HIF‐1α protein stability and that loss of Cezanne stimulates HIF‐1α degradation via proteasome‐independent routes, possibly through chaperone‐mediated autophagy. Synopsis The Lys11 linkage‐specific deubiquitinase Cezanne is shown to regulate HIF‐1α protein stability. Intriguingly, Cezanne‐mediated stabilization depends on pVHL, but not hydroxylation, and is proteasome‐independent. Cezanne regulates the cellular adaptation to hypoxia by preventing proteasome‐independent degradation of the transcription factor HIF‐1α. Loss of Cezanne results in decreased HIF‐1α target gene expression and increased cell death in hypoxia. HIF‐1α is modified with Lys11‐ and Lys48‐linked ubiquitin conjugates. Cezanne may affect HIF‐1α degradation through chaperone‐mediated autophagy. Graphical Abstract The Lys11 linkage‐specific deubiquitinase Cezanne is shown to regulate HIF‐1α protein stability. Intriguingly, Cezanne‐mediated stabilization depends on pVHL, but not hydroxylation, and is proteasome‐independent.